2009
DOI: 10.1007/978-3-642-02577-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Gesture-Controlled User Input to Complete Questionnaires on Wrist-Worn Watches

Abstract: Abstract. The aim of this work was to investigate arm gestures as an alternative input modality for wrist-worn watches. In particular we implemented a gesture recognition system and questionnaire interface into a watch prototype. We analyzed the wearer's effort and learning performance to use the gesture interface and compared their performance to a classical button-based solution. Moreover we evaluated the system performance to spot wearer gestures and the system responsiveness. Our wearer study showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…Although this practice phase was short, users quickly adopted the gestures during this time. In a related analysis users rated physical effort constantly while the focus on the gestures decreased when performing multiple gesture repetitions [17]. This indicates that such a practicing step is a useful approach for specifically designed gestures, as they are used here.…”
Section: B Dataset and Evaluation Proceduresmentioning
confidence: 78%
See 2 more Smart Citations
“…Although this practice phase was short, users quickly adopted the gestures during this time. In a related analysis users rated physical effort constantly while the focus on the gestures decreased when performing multiple gesture repetitions [17]. This indicates that such a practicing step is a useful approach for specifically designed gestures, as they are used here.…”
Section: B Dataset and Evaluation Proceduresmentioning
confidence: 78%
“…In a related study of user ratings we observed that while the focus on performing the gestures decreases, the effort to execute them remains constant [17]. Hence it is essential to restrict the number of gestures to maintain usability even over weeks and months of continuous usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. use motion sensors embedded in a wrist worn device as input for a questionnaire [1]. However, most gestures in the related work are quite crude compared to the ones used in this paper [9], [14].…”
Section: A Related Workmentioning
confidence: 98%
“…There are also quite a number of data gloves and wearable keyboards. Unfortunately, they all require heavy augmentation of the user's wrist/hand [6], [1], [10], [11]. Additionally, all of these devices use a combination of motion sensors, cameras/light sensors and microphones to perform input or context recognition.…”
Section: A Related Workmentioning
confidence: 99%